Hyphenating Moses : a postcolonial exegesis of identity in Exodus 1:1-3:15 - Roth, Federico Alfredo. (Biblical Interpretation Series, 2017)
Postcolonial biblical criticism took shape, largely, by critiquing the book of Exodus. Because of the eventual dispossession of Canaanites in the conquest narratives, so goes the thinking, the Hebrews' God amounts to little more than a dangerous, destructive, and ethnocentric figure. In Hyphenating Moses Federico Alfredo Roth challenges this consensus by providing an alternative reading of its early narratives (1:1-3:15). Redeploying postcolonial theory and themes, Roth presents a reading of these well-known scenes as orbiting around the topic of identity formation, climaxing in the burning bush episode. In the giving of the name, YHWH promotes the virtue of conceiving identity as a malleable reality to be sought after by all parties caught in the dehumanizing discourse of colonial subjugation.